Treatment outcomes in NTM-PD in a high TB burden context - S. Kang; J.E. Schmidt; I. Chen; S. Tiberi (IJTLD Open)
BACKGROUND: Non-tuberculous mycobacterial (NTM) pulmonary disease (PD) is a significant concern in China, compounding the existing burden of TB. This review aims to summarise the treatment outcomes for NTM-PD in China. METHODS: We reviewed the evidence on NTM-PD, including treatment regimens and clinical outcomes, from 17 studies identified through screening of three Chinese biomedical databases. RESULTS: Antimicrobial treatment showed a microbiological cure rate ranging from 17.2% to 60.0% in studies with ≥50 NTM-PD patients, with lower rates observed among older and malnourished patients. The Mycobacterium chelonae abscessus group (MC-AG) and Mycobacterium avium-intracellulare complex (MAC) were the most prevalent NTM species in China. Higher microbiological cure rates were seen in MAC PD compared with MC-AG PD. The addition of cefoxitin and linezolid improved culture conversion rates in MC-AG-infected patients. One study ( n = 24) demonstrated that resecting lesions and chemotherapy led to more favourable clinical outcomes. CONCLUSION: Treatment regimens recommended in Chinese guidelines yielded poor-to-moderate outcomes for NTM-PD in China, highlighting the need for further research into alternative antimicrobial treatments to improve efficacy.